ISOTHERMAL PYROLYSIS OF KRAFT PULP MILL SLUDGE - Syamsudin Syamsudin; Herri Susanto; Subagjo Subagjo (Dept. of Chemical Engineering, Diponegoro University, 2013)
Kraft pulp mill sludge cake composed of rejected wood fibers and activated sludge microorganisms. With a heating value about 14 MJ/kg (dried basis), this type of biomass had a potential as an alternative energy source. Unfortunately, it had an ash content of 27.6% and a moisture content of 80%. For reducing moisture content with minimum energy consumption, a combination of mechanical dewatering and thermal drying was studied previously. Meanwhile, experiments on isothermal pyrolysis had been carried out for further improvement on ultimate and proximate analysis of solid fuel. Final mass of char obtained from pyrolysis at 500oC was not significantly different from that of 700oC, so pyrolysis was considered to be optimum at 500oC. A char obtained from pyrolysis at temperature of 500oC had a pore surface area of 77.049 m2/g (highest among other temperatures). Kinetic of isothermal pyrolysis was well represented with a first order modified volumetric model with a frequency factor of 0.782 1/s and an activation of 34.050 kJ/mol.